Tinjauan Strategis Pendidikan Islam Moderat Dalam Bingkai Kearifan Lokal Budaya Melayu - Ahmad Yani; Sufi Nisa Athahirah; Hikmatul Hidayah (Institut Agama Islam Hidayatullah Batam, 2025)
This study examines the Strategic Review of Moderate Islamic Education within the framework of local Malay cultural wisdom. The research method used is library research with a descriptive qualitative approach, where data is analyzed conceptually to illustrate the relationship between moderate Islamic values and elements of Malay culture. The results show that the Malay cultural values inherited through Tunjuk Ajar Melayu are very much in line with moderate Islamic teachings. These values reflect Islamic moral and social teachings that prioritize harmony, justice, and respect for others. Furthermore, Malay culture has also long taught the importance of good manners in interactions, etiquette, and a collective spirit that aligns with the principle of moderation in Islamic education. The integration of moderate Islamic education with local Malay cultural wisdom can produce a contextual and applicable educational model. This model is not only able to instill inclusive and anti-extremist Islamic values but also strengthens love for local culture that is increasingly eroded by the current of modernity.